Legal Sales and Moral of Businessmen Islamic Jurisprudence in the Shahih Bukhari Book Chapter: Sales | ما يجوز من البيوع وأخلاق البائعين من الأحكام الفقهية في كتاب البيوع من صحيح البخاري - Desmadi Saharuddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2010)
This article concludes that many types of sale such as Ajal Sale, al Misk Sale, alMuzayadah Sale and al Fudluli Sale, according to the imam Bukhari perspective arelegal, as mentioned in the Sahih Bukhari Book, chapter of al Buyu’(sales). Ajal Sale is atype of sale by postponement payment system. Imam Bukhari argues for the legality ofthat sale by the Hadis; that Prophet Muhammad Saw ever bought a food from a oneJew by pawning his iron clothes. Its mean he paid the price of food after few days later.About the legality of Al Misk (perfume) Sale, Imam Bukhari argues by the hadis thatProphet Muhammad made a parable between a perfume seller and a blacksmith. Also,most of Moslem scholars agreed that perfume is pure (thahir) and allowed for sale.Muzayadah Sale is someone gives a certain price for buyer, and gives another buyerwith a different price, more expensive than the first price. Al Fudluli Sale is someonebuys goods for someone (owner of money) without his permission, and then theowner agrees with that sale. The writer used a comparative method, which compareddifferent views of the classic Muslim scholars (Muslim Jurisprudence)